Kinetic analysis and modeling of L-valine production in fermentation batch from E. coli using glucose, lactose and whey as carbon sources (2021)
ABSTRACT: In this study the effect of the carbon source on L-valine production kinetics using genetically modified E. coli was researched. Glucose, lactose, Whey (W) and deproteinized whey (DW) were tested as carbon sources, keeping the carbon/nitrogen (C/N) ratio constant. Biomass generation and substrate consumption were modeled with Contois and Mass Conservation models, respectively, whereas Mass Conservation Balance and Luedeking-Piret models were used for product obtaining. Results showed that L-valine production is partially associated to growth, with values of 0.485 g L-valine/(g dry cell weight.h), and a product loss effect at a specific rate (β) of 0.019 g L-valine/(g dry cell weight.h) with W. The yield of this product increased 36 % using W concerning glucose or lactose as carbon sources. On the other hand, Mass Balance and Luedeking-Piret models adjust properly to experimental data (R2 >0.90). In conclusion whey is a promising substrate for obtaining L-valine using genetically-modified E. coli.